Penerapan Aquaponic Sebagai Teknologi Tepat Guna Pengolahan Limbah Cair Kolam Ikan di Dusun Kergan, Tirtomulyo, Kretek, Bantul, Yogyakarta - Nur Annisa Maharani; Pinjung Nawang Sari (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2016)
Kergan sub-village is located in the Tirtomulyo Village, Kretek District, Bantul Regency, on the process into a tourist village. Cultivation of carp and catfish become a favored activity in the village because most of the citizen has carp and catfish ponds for those will be used as priority to become a Tourism Village of Carp. However, the fish pond waste has become a problem. During this time the waste just being dumped into the environment, that cause a contamination on water wells. Therefore, solution to treat this fish pond waste in the village is necessary to be solved by community service activities. This community service activities concluded that making aquaponic is one of the solution. Public education, consultation and mentoring are the most effective 3 methods in solving the problems that exist in the village. The benefits of those activities that provide new knowledge about waste treatment pond fish and provide new skills in making aquaponics.